HUBUNGAN BODY MASS INDEKS DAN FARTLEK TERHADAP VO2MAX DI SMP RAHADI OSMAN PONTIANAK - Sumarlin, Adrianus; Supriatna, Eka; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The purpose of this study is to determine whether there is a relationship and how closely the relationship of Body Mass Index and Fartlek to VO2Max on Learners at SMP Rahadi Osman Pontianak.The method used to explain this research is Quantitative Descriptive method by using Corelationship Studies form. Sampling technique using purposive sampling. Samples studied were Junior High School Students in Rahadi Osman Pontianak as many as 15 people. Data analysis was performed using correlation test using computerized system (SPSS 21).From result of calculation of correlation test by using SPSS Version 21 found sig value = 0,04% <0,05% with value of corelation corporation equal to 0,507%. This indicates that Body Mass Index positively correlate to VO2Max Student in SMP Rahadi Osman Pontianak with the degree of moderate correlation and Fartlek correlation positively correlated with a significance value of 0.02% <0.05% of the VO2Max learner at SMP Rahadi Osman Pontianak with a strong correlation degree with a correlation of 0.609%.Keywords: Body Mass Index, Fartlek, VO2Max